The effect of SNPs on expression levels in Nimblegen RNA expression microarrays. (2015) - Lund, Sigrun Helga; Sigurdsson, Asgeir; Gudjonsson, Sigurjon Axel; Gudmundsson, Julius; Gudbjartsson, Daniel Fannar; Rafnar, Thorunn; Stefansson, Kari; Stefansson, Gunnar
In this paper the effect of SNPs on expression levels in Nimblegen RNA expression microarrays is investigated. A vast number of replicates of probe pairs representing both alleles of SNPs on 14 loci allows accurate estimation of the difference in signal intensities both within and between probe pairs. The majority of probepairs with sufficiently high expression have significant differences in expression levels within the pair and the difference shows concordance with the genotype of the samples. With two or more replicates of each probe, the alleletoallele variance dominates the error in estimating the difference within the probepair, ten replicates are needed for adequate power in calling a true difference within a single probepair. Using the expression level of the probe within the probepair that has the higher value gives more accurate estimates. When using probes at loci containing known SNPs one should use probes containing both alleles of the SNP.